Internet-based learning in improving student digital literacy - Apriani Riyanti; Unggul Sagena; Nana Citrawati Lestari; Susatyo Adhi Pramono; Gamar Al Haddar (Institute of Computer Science (IOCS), 2023)
Internet-based education has become an integral aspect of contemporary education and plays a crucial role in enhancing the digital literacy of elementary school students. With learning tools and applications, elementary school kids can enhance their digital abilities and comprehend topics and principles in a more dynamic, entertaining, and efficient manner. In addition, internet-based learning helps students prepare for an increasingly technological future and improves their teamwork and communication abilities. Nonetheless, schools and educational institutions must ensure that students receive the required training and direction to enhance their digital literacy through internet-based learning. The purpose of this research is to identify factors that influence the digital literacy of elementary school students through internet-based learning, analyze the information synthesis, and provide recommendations and suggestions for schools and educational institutions to improve the digital literacy of elementary school students through internet-based learning, namely the development of internet-based learning media in an effort to evaluating and comprehending how internet-based learning influences the digital literacy of elementary school students is necessary for research purposes to determine the function of internet-based learning in enhancing the digital literacy of primary school students.